Causative source of Mw 6.9 Sikkim–Nepal border earthquake of September 2011: GPS baseline observations and strain analysis - Pradhan, Rashmi; Prajapati, Sanjay K.; Chopra, Sumer; Kumar, Ashok; Bansal, B.K.; Reddy, C.D. (My University, 2013)
The recent earthquake of Mw 6.9 which occurred on September 18, 2011 in Sikkim–Nepal border region (epicenter 27.72°N, 88.06°E, depth 20.7 km, ∼68 km NW of the Capital city Gangtok) is the strongest earthquake in the instrumentally recorded history of the region. The fault plane solution of this earthquake indicates a strike-slip motion. However, the seismological and geological studies carried out so far after the earthquake could not confirm the causative fault plane. In the present study, GPS observations are used to ascertain causative source in the generation of earthquake and its correlation with the observed seismic data of the region. The co-seismic displacements recorded by GPS show maximum displacement of ∼11 mm at Phodong and ∼9 mm at Taplejung station, near the epicenter. A simple rigid cross fault model using GPS baseline observations was employed to figure out the causative fault plane and seismological characteristic of the region. It is inferred that the movement represents the kinematic adjustment of the subsidiary faults as a result of the displacement along the NW–SE principal plane. Strain analysis using GPS baseline inferred that the region southeast of epicenter has undergone large deformation. In addition, a significant part of the measured deformation across the surface fault zone for this earthquake can be attributed to post-seismic creep.
Keywords: GPS baseline; Fault movement; Riedel shear; Strain